Hotel Marketing Strategy in Biak Papua to Survive During the Covid-19 Pandemic - Andi Sahat Maasi Sigalingging; Dominggus Rudolf Leiwakabessy (PINISI Discretion Review, 2021)
The pandemic has paralyzed global tourism. In Biak Papua, the impact of the pandemic on the tourism industry is enormous. Almost all hotels stop operating, even if one is open, that also opens up for the quarantine of Covid sufferers. This article examines the condition of hotels in Biak and the survival marketing strategies adopted during the outbreak. This research uses a descriptive qualitative approach using in-depth interviews and literature studies on books, scientific journals, and online news. This study focuses on Basana Inn and Manna Inn, on the grounds of the level of representation of the Jasmine Hotel and customer types. The research results show that the impact of the pandemic has resulted in almost empty hotel occupancy. The strategy carried out is almost the same, namely by terminating employees permanently and temporarily, limiting the use of hotel facilities, spending efficiency, selling non-room products online, and refusing to refund bookings by changing visit schedules. During the Covid 19 pandemic, a marketing strategy is very important to do. In obtaining optimal results, strategies in marketing are carried out which have a very broad scope, including analytical strategies to face competition, price strategies, product strategies, service strategies and so on. The Covid 19 outbreak has given service companies a sense of worry or discomfort, especially the Basana Inn Hotel which is engaged in accommodation services. Seeing the results of the identification of problems in this study, researchers are interested in researching the title "Hotel Marketing Strategies in Biak Papua to Survive the Covid-19 Pandemic." The purpose of this research is to find out and analyze the most appropriate strategy in the Covid 19 Pandemic situation.